Fungal communities in Florida salt marsh mosquito midguts vary between species and over time but have low structure - Pérez-Ramos, Daniel W.; Caragata, Eric P. (Frontiers in Immunology, 2025)
IntroductionMicroorganisms are intrinsically tied to the developmental and reproductive success of mosquitoes, can influence their ability to resist insecticides, and can strongly influence their ability to harbor and transmit pathogens of medical importance. Although mosquito-associated fungi have oben been overlooked at the expense of bacteria, several different fungal taxa are known to modulate interactions between mosquitoes and pathogens, while others have potential applications as biopesticides due to their entomopathogenic activity. Accordingly, understanding how and why different fungi associate with mosquito tissues is an important step toward elucidaUng the impact the diverse kingdom of microorganisms has on mosquito biology and mosquito- borne disease.MethodsIn this study, we used Illumina Mi-Seq profiling of the internal transcribed spacer gene to characterize the midgut mycobiota of field collected adult mosquitoes from three species: Aedes taeniorhynchus, Anopheles atropos, and Culex nigripalpus, at two different collection times.ResultsWe observed that all mosquito specimens carried high loads of Rhodotorula lamellibrachiae, a common environmental yeast that is known to be involved in nitrogen fixation, although its role in mosquito biology is not clear. We also find that the mycobiome is strongly influenced by mosquito species, that few fungi have both high abundance and prevalence, and that few fungi consistently co- associate across time and host species.DiscussionThese findings suggest that there is limited structure to mosquito associated fungal communities, implying that their assembly may be more driven by stochastic than deterministic processes. Our findings highlight the influence of key variables on mosquito fungal diversity and help facilitate understanding of how and when mosquitoes acquire fungi and the roles that fungi play in mosquito biology.